Liberation day : [large type] stories - Saunders, George, 1958- (Thorndike Press, a part of Gale, a Cengage Company, 2022)
In his stories, Saunders explores ideas of power, ethics, and justice, and cuts to the very heart of what it means to live in community with our fellow humans. Wickedly funny, unsentimental, and perfectly tuned, the stories challenge and surprise as they encompass joy and despair, oppression and revolution, bizarre fantasy and brutal reality. -- adapted from back cover